A biomechanical study on the laminate stacking sequence in composite bone plates for vancouver femur B1 fracture fixation. (November 2020) - Dhason, Raja; Roy, Sandipan; Datta, Shubhabrata
Highlights: 3D finite-element analysis provides an effective pre-operative method for vancouver femur B1 fracture fixation for planning customized implants. The designed composite bone plate absorbing the impact of the mechanical forces generating during daily activities. The metal bone plate fixation can replace by composite bone plate. Abstract: Background and objectives: Composite bone plates are proposed for fracture fixation in periprosthetic femoral fracture. Metallic plates, having high stiffness compared to bone lead to stress shielding, reduce the compression force in the fracture site, affectthe healing process. Reduction of stiffness in the axial direction due to above reason without lowering the stiffness in transverse to avoid much of shear strain and thus avoiding instability at the fracture site leads to selective stress shielding. This can only be achieved through meticulously designed fiber reinforced composite. In the present work varied fiber orientations in the stacked laminates with varied fiber types are employed in a post-operative femur fixation for the in-silico analyses of their effectiveness using finite element analysis. Methods: In this study a Total Hip Arthroplasty (THA) model is constructed with composite bone plates. Three-dimensional narrow type metal plate is modeled with 12 holes and length of 194 mm. Three different types of composite bone plates are modeled with 12 holes of different size for the analysis i.e. Type 1 (5.6 mm thickness and 16 mm width), Type 2 (6 mm thickness and 16 mm width) and Type 3(6 mm thickness and 18 mm width). Anatomical 3D FE models of THA with composite bone plates are constructed to find out the interfacial stresses and strains. The finite element software ANSYS is used to perform the analysis. Results: A three-dimensional FE model of immediately post-operative femur fixation is developed and studied the maximum stress distribution, strain and movement in axial/shear direction in the metal and composite bone plate near to the fracture site. In the present study, the metal and composite plate (carbon/epoxy, glass/epoxy and flax/epoxy) used for most common Vancouver type B1 fracture to observe the biomechanical behavior of different models in IPO condition using FEA. Conclusions: Optimizing the fiber orientations of composite bone plates of Total Hip Arthroplasty (THA) model by controlling the biomechanical stresses could be a favorable approach. The finite element analysis approach gives a viable solution to design the composite bone plate and for designing future models that preserves the biomechanical function of THA with composite bone plate. Graphical abstract: Image, graphical abstract